Titanium Implant

KR103017168B1Active Publication Date: 2026-09-11KOREA INSTITUTE OF INDUSTRIAL TECHNOLOGY
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
KR1020220114927
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Filing Date
2022-09-13
Publication Date
2026-09-11
Estimated Expiration
2042-09-13

Smart Images

  • Figure 112022095603214-PAT00001_ABST
    Figure 112022095603214-PAT00001_ABST
Patent Text Reader

Abstract

According to one embodiment of the present invention, an implant is provided comprising: a titanium implant substrate; a porous layer having a plurality of pores formed on the surface of the titanium implant substrate; and a nanopattern layer formed on the porous layer.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to a titanium implant, and more specifically, to providing an implant having a nanopattern formed by surface modification of the titanium implant. Background Technology

[0003] Implants must be manufactured using highly biocompatible materials that are stable for biological tissues, ensuring no side effects and no inducing chemical or biochemical reactions. Furthermore, after implantation, they must have high osseointegration strength, ensuring that the space between the bone and the implant is filled entirely with bone without any soft tissue intervening. Additionally, they must be manufactured from materials with very high mechanical strength to prevent deformation or failure.

[0004] In order to satisfy the above conditions, various metals and alloys have been developed as suitable materials for implants, but problems have arisen that implants cannot satisfy the requirements for biomaterials, such as biocompatibility, chemical compatibility, and mechanical compatibility. To solve the above problems, various types of bioceramics have been developed, but most ceramics are weak against impact and difficult to process, so they cannot be used alone for the manufacture of implants.

[0005] Currently, various metals and alloys are being developed as suitable materials for implants, but titanium metal and its alloys are still primarily used. For example, titanium and titanium alloys possess many advantages, such as ease of processing, high biocompatibility with human tissues, biocompatibility, and high mechanical strength. However, titanium and titanium alloys themselves have disadvantages, such as a long time for bone integration when implanted in the human body, and the fact that metal ions can leach into the body and have adverse effects after a long period following implantation. To overcome these drawbacks, active technological development is underway to strengthen bone integration by appropriately treating the material surface.

[0007] Against this backdrop, the inventors completed the present invention by confirming the effect of enhancing the response to osteocytes by securing porous roughness on the surface of a titanium implant.

[0008] delete Prior art literature

[65535] Korean Patent Publication No. 10-1724039 (April 6, 2017) The problem to be solved

[0009] One objective of the present invention is to provide an implant having a plurality of pores on its surface and a micro-roughness formed thereon. means of solving the problem

[0011] This is explained in detail as follows. Meanwhile, each description and embodiment disclosed in the present invention may be applied to each other description and embodiment. That is, all combinations of the various elements disclosed in the present invention fall within the scope of the present invention. Furthermore, the scope of the present invention should not be considered limited by the specific descriptions provided below.

[0013] A first aspect of the present invention for achieving the aforementioned objective provides an implant comprising: a titanium implant substrate; a porous layer having a plurality of pores formed on the surface of the titanium implant substrate; and a nanopattern layer formed on the porous layer.

[0015] Additionally, a second aspect of the present invention provides an implant comprising at least one selected from Ti-6Al-4V, Ti-6Al-7Nb, Ti-13Nb-13Zr, Ti-15Mo, Ti-35.3Nb-5.1Ta-7.1Zr, Ti-30Nb, Ti-29Nb-13Ta-2Sn, Ti-29Nb-13Ta-4.6Sn, Ti-29Nb-13Ta-6Sn, Ti-16Nb-13Ta-4Mo, and Ti-29Nb-13Ta-4.6Zr.

[0017] In addition, a third aspect of the present invention provides an implant in which the porous layer is formed with an average roughness (Ra) of 2㎛ to 4㎛.

[0019] In addition, a fourth aspect of the present invention provides an implant in which the nanopattern layer is formed after anodizing treatment.

[0021] In addition, a fifth aspect of the present invention provides an implant in which the pore size of the nanopattern layer is 70 nm to 150 nm.

[0023] In addition, a sixth aspect of the present invention provides an implant in which the average roughness (Ra) of the implant surface is formed to be 1.5㎛ to 2.5㎛. Effects of the invention

[0025] The implant according to the present invention can secure a micro-porous roughness, thereby providing an enhanced osseointegration response. Brief explanation of the drawing

[0027] FIG. 1 is a figure showing an anodic oxidation apparatus according to one embodiment of the present invention. Figure 2 is an SEM image showing the implant surface after sandblasting powder particles of sizes 50 μm, 150 μm, and 250 μm according to one embodiment of the present invention. Figure 3 is an SEM image showing the implant surface after sandblasting powder particles of 50 μm size according to one embodiment of the present invention and then etching them in a mixed solution of hydrochloric acid and sulfuric acid at 80°C to 100°C for 5 minutes. Figure 4 is an SEM image showing the implant surface after sandblasting powder particles of 50 μm size according to one embodiment of the present invention and then etching them in a mixed solution of hydrochloric acid and sulfuric acid at 80°C to 100°C for 10 minutes. Figure 5 is an SEM image showing the implant surface after sandblasting powder particles of 50 μm size according to one embodiment of the present invention and then etching them in a mixed solution of hydrochloric acid and sulfuric acid at 80°C to 100°C for 15 minutes. Figure 6 is an SEM image showing the implant surface after sandblasting powder particles of 150 μm size according to one embodiment of the present invention and then etching them in a mixed solution of hydrochloric acid and sulfuric acid at 80°C to 100°C for 5 minutes. Figure 7 is an SEM image showing the implant surface after sandblasting powder particles of 150 μm size according to one embodiment of the present invention and then etching them in a mixed solution of hydrochloric acid and sulfuric acid at 80°C to 100°C for 10 minutes. Figure 8 is an SEM image showing the implant surface after sandblasting powder particles of 150 μm size according to one embodiment of the present invention and then etching them in a mixed solution of hydrochloric acid and sulfuric acid at 80°C to 100°C for 15 minutes. Figure 9 is an SEM image showing the implant surface after sandblasting powder particles of 250 μm size according to one embodiment of the present invention and then etching them in a mixed solution of hydrochloric acid and sulfuric acid at 80°C to 100°C for 5 minutes. Figure 10 is an SEM image showing the surface of an implant after sandblasting powder particles of 250 μm size according to one embodiment of the present invention and then etching them in a mixed solution of hydrochloric acid and sulfuric acid at 80°C to 100°C for 10 minutes. Figure 11 is an SEM image showing the implant surface after sandblasting powder particles of 250 μm size according to one embodiment of the present invention and then etching them in a mixed solution of hydrochloric acid and sulfuric acid at 80°C to 100°C for 15 minutes. FIG. 12 is a graph showing the change in roughness according to powder particle size and etching time according to one embodiment of the present invention. FIG. 13 is an SEM image showing the surface, cross-section, and bottom surface of an oxide film produced after anodic oxidation according to one embodiment of the present invention. FIG. 14 is an SEM image showing the surface, cross-section, and bottom surface of an oxide film produced after anodic oxidation according to one embodiment of the present invention. Figure 15 is an SEM image showing a nanopatterned surface produced by sandblasting powder particles of 50 μm size according to one embodiment of the present invention, etching them in a mixed solution of hydrochloric acid and sulfuric acid at 80°C to 100°C for 5 minutes, and then anodic oxidation. Figure 16 is an SEM image showing a nanopatterned surface produced by sandblasting powder particles of size 50 μm according to one embodiment of the present invention, etching them in a mixed solution of hydrochloric acid and sulfuric acid at 80°C to 100°C for 10 minutes, and then anodic oxidation. Figure 17 is an SEM image showing a nanopatterned surface produced by sandblasting powder particles of size 50 μm according to one embodiment of the present invention, etching them in a mixed solution of hydrochloric acid and sulfuric acid at 80°C to 100°C for 15 minutes, and then anodic oxidation. FIG. 18 is an SEM image showing a nanopatterned surface produced by sandblasting powder particles of 150 μm size according to one embodiment of the present invention, etching them in a mixed solution of hydrochloric acid and sulfuric acid at 80°C to 100°C for 5 minutes, and then anodic oxidation. Figure 19 is an SEM image showing a nanopatterned surface produced by sandblasting powder particles of 150 μm size according to one embodiment of the present invention, followed by etching in a mixed solution of hydrochloric acid and sulfuric acid at 80°C to 100°C for 10 minutes, and then anodic oxidation. FIG. 20 is an SEM image showing a nanopatterned surface produced by sandblasting powder particles of 150 μm size according to one embodiment of the present invention, etching them in a mixed solution of hydrochloric acid and sulfuric acid at 80°C to 100°C for 15 minutes, and then anodic oxidation. Figure 21 is an SEM image showing a nanopatterned surface produced by sandblasting powder particles of 250 μm size according to one embodiment of the present invention, etching them in a mixed solution of hydrochloric acid and sulfuric acid at 80°C to 100°C for 5 minutes, and then anodic oxidation. FIG. 22 is an SEM image showing a nanopatterned surface produced by sandblasting powder particles of 250 μm size according to one embodiment of the present invention, followed by etching in a mixed solution of hydrochloric acid and sulfuric acid at 80°C to 100°C for 10 minutes, and then anodic oxidation. FIG. 23 is an SEM image showing a nanopatterned surface produced by sandblasting powder particles of 250 μm size according to one embodiment of the present invention, followed by etching in a mixed solution of hydrochloric acid and sulfuric acid at 80°C to 100°C for 15 minutes, and then anodic oxidation. FIG. 24 is an SEM image showing the surface after removing the oxide film formed after anodic oxidation according to one embodiment of the present invention. FIG. 25 is a graph showing the surface roughness after removing the oxide film formed after anodic oxidation according to one embodiment of the present invention. Specific details for implementing the invention

[0028] The present invention will be explained in more detail below through examples. These examples are intended to explain the invention more specifically, and the scope of the invention is not limited by these examples.

[0029] The present invention is capable of various modifications and may take various forms, and specific embodiments are illustrated in the drawings and described in detail in the text. However, this is not intended to limit the invention to the specific disclosed forms, and it should be understood that the invention includes all modifications, equivalents, and substitutions that fall within the spirit and scope of the invention.

[0030] In describing each drawing, similar reference numerals have been used for similar components. In the attached drawings, the dimensions of the structures are depicted enlarged from their actual size for clarity of the invention. Terms such as "first," "second," etc., may be used to describe various components, but said components should not be limited by said terms. These terms are used solely for the purpose of distinguishing one component from another. For example, without departing from the scope of the invention, the first component may be named the second component, and similarly, the second component may be named the first component. A singular expression includes a plural expression unless the context clearly indicates otherwise.

[0031] In this application, terms such as "comprising" or "having" are intended to specify the existence of the features, numbers, steps, actions, components, parts, or combinations thereof described in the specification, and should be understood as not precluding the existence or addition of one or more other features, numbers, steps, actions, components, parts, or combinations thereof. Furthermore, when a part such as a layer, film, region, or plate is described as being "on" another part, this includes not only cases where it is "immediately above" another part, but also cases where there is another part in between.

[0032] Furthermore, in this specification, when a part such as a layer, film, region, or plate is described as being formed on another part, the direction in which it is formed is not limited to the upward direction only, but also includes being formed in the lateral or downward direction. Conversely, when a part such as a layer, film, region, or plate is described as being "below" another part, this includes not only the case where it is "immediately below" another part, but also the case where there is another part in between.

[0033] In this specification, "upper surface" and "lower surface" are used as relative concepts to facilitate understanding of the technical concept of the present invention. Therefore, "upper surface" and "lower surface" do not refer to specific directions, locations, or components, and are interchangeable. For example, "upper surface" may be interpreted as "lower surface," and "lower surface" may be interpreted as "upper surface." Accordingly, "upper surface" may be referred to as "first" and "lower surface" as "second," or "lower surface" may be referred to as "first" and "upper surface" as "second." However, within a single embodiment, "upper surface" and "lower surface" are not used interchangeably.

[0035] According to one embodiment of the present invention, a titanium implant having a surface of micro-roughness and comprising a plurality of pores can be provided.

[0036] The present invention provides an implant comprising: a titanium implant substrate; a porous layer having a plurality of pores formed on the surface of the titanium implant substrate; and a nanopattern layer formed on the porous layer.

[0038] The above titanium implant substrate may include at least one selected from Ti-6Al-4V, Ti-6Al-7Nb, Ti-13Nb-13Zr, Ti-15Mo, Ti-35.3Nb-5.1Ta-7.1Zr, Ti-30Nb, Ti-29Nb-13Ta-2Sn, Ti-29Nb-13Ta-4.6Sn, Ti-29Nb-13Ta-6Sn, Ti-16Nb-13Ta-4Mo, and Ti-29Nb-13Ta-4.6Zr, but is not limited thereto. The material of the titanium implant substrate may be determined by considering the use and shape of the final product to be manufactured. A titanium implant substrate can be provided with titanium as the main component, and a polished titanium implant substrate having macroscopic roughness on the surface can be provided by sandblasting on the titanium implant substrate, and a surface-modified titanium implant having multiple pores on the surface and microscopic roughness can be manufactured by etching the macroscopic roughness on the surface of the polished titanium implant substrate.

[0039] The above titanium implant substrate is a device inserted or fitted into the body, and the shape of the titanium implant substrate can be determined by considering the shape of the graft required by the body. For example, the titanium implant substrate may have a shape such as a square, circle, ellipse, trapezoid, rhombus, or triangle on a flat surface. In addition, the surface of the implant substrate may include micro-roughness with varying heights to enhance adhesion.

[0041] The above porous layer may be formed by etching after sandblasting treatment.

[0042] The above titanium implant substrate can be provided with foreign substances or organic components removed from its surface. Specifically, the foreign substances can be physically removed, and the method of physical removal can be performed by washing or an air blow method. The removal of the foreign substances allows for effective sandblasting treatment.

[0043] The above sandblasting may refer to a process of cleaning a surface by spraying sand or powder particles from a nozzle together with high-pressure air and causing them to collide with the surface of a substrate.

[0044] The above sandblasting treatment may provide macroscopic roughness to the surface.

[0045] The above macro roughness is higher than the micro roughness and represents a surface roughness of 0.5 mm or more obtained at the measurement distance of a contact-type surface roughness meter.

[0046] The above sandblasting treatment removes powder particles with a size of 200 µm to 300 µm at 3 kgf / cm² 2 Up to 5 kgf / cm 2 It may be performed by sandblasting for 20 to 40 seconds under pressure conditions.

[0047] Specifically, if the size of the powder particles is less than 200 μm, the surface roughness may be lowered to 2.0 μm or less, which may reduce adhesion, and if the size exceeds 300 μm, the surface roughness may be higher to 3.0 μm or more, which may prolong the etching time.

[0048] The above sandblast pressure condition is 3 kgf / cm² 2 If it is less than 5 kgf / cm², the surface treatment effect by blasting is low, so the final surface roughness after etching may be low, and 5 kgf / cm² 2 If exceeded, conversely, the final surface roughness may appear high.

[0049] If the sandblasting time is less than 20 seconds, uniform sandblasting may not be achieved on the surface, and if it exceeds 40 seconds, it may be difficult to remove the sandblasting particles.

[0050] The above powder particles may include TiO2, SiO2, and Al2O3, but are not limited thereto.

[0051] Sandblasting is a process of spraying powder particles onto the surface of a titanium implant substrate to form macroscopic roughness on the surface. The macroscopic roughness may be intended to increase the surface roughness of the implant and provide pores due to the blasting.

[0052] Prior to performing the above etching process, an ultrasonic decomposition step to remove foreign substances on the polished titanium implant substrate may be further performed.

[0054] Next, the above-mentioned macroscopic roughness on the surface of the titanium implant substrate is etched to prepare a porous layer containing a plurality of pores on the surface.

[0055] The above etching refers to the process of engraving a shape by corroding the surface of a metal or substrate.

[0056] The above etching is performed using an acid etching solution, and the acid etching solution may include hydrochloric acid, sulfuric acid, and distilled water, but is not limited thereto.

[0057] The above acid etching solution may comprise the above hydrochloric acid in a ratio of 25 to 35 parts by weight, the above sulfuric acid in a ratio of 20 to 30 parts by weight, and the above distilled water in a ratio of 40 to 50 parts by weight.

[0058] If the weight of the hydrochloric acid is less than 25 parts by weight, uniform etching may not occur, and if it exceeds 35 parts by weight, color change and non-uniformity of the surface may occur due to over-etching.

[0059] If the weight of the sulfuric acid is less than 20 parts by weight, the etching may be slow or not uniform, and if it exceeds 30 parts by weight, color change and non-uniformity of the surface may occur due to over-etching.

[0060] If the above-mentioned distilled water weight is less than 40 parts by weight, color change and non-uniformity of the surface may occur due to over-etching, and if it exceeds 50 parts by weight, the etching speed may be slow and the process time may be prolonged.

[0061] The concentration of the hydrochloric acid may be 30 wt% to 40 wt%, and the concentration of the sulfuric acid may be 80 wt% to 100 wt%.

[0062] If the above hydrochloric acid concentration is less than 30 wt%, the etching process time may be prolonged, and if it exceeds 40 wt%, color change and non-uniformity of the surface may occur due to over-etching.

[0063] If the above sulfuric acid concentration is less than 80 wt%, the etching process time may be prolonged, and if it exceeds 100 wt%, surface color change and non-uniformity may occur due to surface over-etching.

[0064] The above etching may be performed by stirring at 100 rpm to 300 rpm for 3 to 20 minutes at 80 ℃ to 100 ℃.

[0065] If the above etching performance temperature is less than 80 ℃, the etching process time may be prolonged, and if it exceeds 100 ℃, distilled water in the etching solution may vaporize, and the composition of the etching solution may change.

[0066] If the above etching execution time is less than 3 minutes, the surface etching may not occur uniformly, and if it exceeds 20 minutes, the process time may increase and become unnecessary.

[0067] After etching, an ultrasonic decomposition step to remove foreign substances on the porous layer can be further performed.

[0068] The above etching can provide a reduction in the work process and an increase in production volume by performing the process at a high temperature for a short time in a high-temperature and high-concentration acid etching solution.

[0069] The sandblasting and etching described above must be performed sequentially. Specifically, sandblasting may be performed on a titanium implant substrate to form macroscopic roughness. However, if only sandblasting is performed, the medium remaining on the surface may hinder osseointegration and reduce surface stability. Therefore, the present invention provides increased adhesion by facilitating osseointegration through the formation of microscopic roughness and fine holes—which are lower than the surface stability and macroscopic roughness—by etching, thereby providing a surface area capable of adhesion with small, irregular shapes.

[0070] The above micro roughness refers to the surface roughness obtained at the measurement distance of a contact-type surface roughness meter, representing a surface roughness of 1 μm to 0.5 mm.

[0071] The above micro roughness (Ra) may be formed with an average roughness of 2 μm to 4 μm.

[0072] The above plurality of pores may be formed with pores ranging in size from 1 μm to 3 μm across the entire surface.

[0074] Next, a nanopattern layer formed on the porous layer is prepared.

[0075] The above nanopattern layer may be formed as a mark remaining after the removal of the nanotube-shaped oxide film generated after anodizing treatment.

[0076] The anodic oxidation described above is an oxidation reaction that occurs at the anode in electrolysis. Since current flows in the direction in which electrons move from the compound in the electrolyte to the inside of the electrode, the compound is oxidized by having electrons taken away, and cathodic reduction occurs in response. Therefore, it refers to an electrochemical method in which a metal or semiconductor is subjected to anodic polarization treatment in an electrolyte to create an oxide film on the surface, and the resulting film is dense and robust, serving to protect the metal inside.

[0077] The above anodic oxidation may be performed at an applied voltage of 30V to 80V for 10 to 50 minutes.

[0078] In the above-mentioned anodic oxidation, if the applied voltage is less than 30V, the anodic oxidation process time may be prolonged, and if it exceeds 80V, it may be difficult to form a uniform oxide film. Additionally, if performed for less than 10 minutes, it may be difficult to create a uniform nanotube-shaped oxide film, and if it exceeds 50 minutes, the process time may be prolonged, leading to a decrease in production efficiency.

[0079] The anodic oxidation described above may be performed under solvent conditions comprising at least one selected from ethylene and ammonium fluoride.

[0080] The oxide film formed after the above anodic oxidation can be removed by performing the process at an applied voltage of 1 V to 5 V for 1 minute to 5 minutes.

[0081] If the applied voltage for the above oxide film removal is less than 1V, the oxide film may not be completely removed, and if it exceeds 5V, it is difficult to control uniform oxide film removal and may affect the deformation of the exposed titanium implant substrate due to oxide film removal. Additionally, if performed for less than 1 minute, the oxide film may not be completely removed, and if performed for more than 5 minutes, it may affect the deformation of the exposed titanium implant substrate due to oxide film removal.

[0082] The oxide film may be formed in the form of nanotubes during an anodic oxidation process, and the nanopattern may be formed as a mark remaining on the surface of a blast-treated titanium implant substrate as the oxide film in the form of nanotubes is removed. Such a nanopattern can provide an effect that can improve biocompatibility.

[0083] The above nanopattern may enhance biocompatibility.

[0084] The pore size of the above nanopattern layer may be 70 nm to 150 nm.

[0085] The average roughness (Ra) of the implant surface may be formed to be 1.5㎛ to 2.5㎛.

[0087] Example 1: Implant surface treatment method

[0088] 1) Prepare a Ti-6Al-4V alloy implant substrate with dimensions of 1.5cm*1.5cm*2mm from which foreign substances have been removed.

[0089] 2) 250 µm Al2O3 powder is applied to the above implant substrate at 4 kgf / cm² through a nozzle size Ø 3.2 2 Sandblasting with pressure (250 μm in Fig. 2).

[0090] 3) Foreign substances on the above implant substrate are cleaned by ultrasonically decomposing them.

[0091] 4) A surface-modified titanium implant substrate is provided by etching with an acid etching solution prepared by mixing 36.46% HCl (30ml), 98.08% H2SO4 (25ml), and distilled water (45ml) on a washed implant substrate while stirring at 200rpm for 5 minutes at 100℃ (Fig. 9).

[0092] 5) Foreign substances on the surface-modified titanium implant substrate are cleaned by ultrasonically decomposing them.

[0093] 6) The surface-modified titanium implant substrate was placed in an anodic oxidation apparatus (Fig. 26) containing 98.0 ml of ethylene glycol, 3.7 g of 0.1 M NH4F, and 2.0 ml of 2.0 wt% H2O solvent, and oxidized at 50 V for 30 minutes.

[0094] 7) After the above anodic oxidation, the oxide film was removed in a 500 ml solution of 1 M H2SO4 at 3 V for 3 minutes.

[0096] FIG. 2 shows Al2O3 powder with sizes of 50 µm, 150 µm, and 250 µm applied to an implant substrate at 4 kgf / cm² for 30 seconds through a nozzle size Ø 3.2. 2 This is an SEM image confirming that macroscopic roughness was formed after sandblasting under pressure.

[0097] Figure 3 is an SEM image showing the implant surface after sandblasting 50 μm size Al2O3 powder and then etching it at 80°C, 90°C, and 100°C for 5 minutes in a solution mixed with different weight parts of 30% hydrochloric acid and 25%, 35%, and 45% sulfuric acid.

[0098] Figure 4 is an SEM image showing the implant surface after sandblasting 50 μm size Al2O3 powder and then etching it at 80°C, 90°C, and 100°C for 10 minutes in a solution mixed with different weight parts of 30% hydrochloric acid and 25%, 35%, and 45% sulfuric acid.

[0099] Figure 5 is an SEM image showing the implant surface after sandblasting 50 μm size Al2O3 powder and then etching it at 80°C, 90°C, and 100°C for 15 minutes in a solution mixed with different weight parts of 30% hydrochloric acid and 25%, 35%, and 45% sulfuric acid.

[0100] Figure 6 is an SEM image showing the implant surface after sandblasting 150 μm size Al2O3 powder and then etching it at 80°C, 90°C, and 100°C for 5 minutes in a solution mixed with different weight parts of 30% hydrochloric acid and 25%, 35%, and 45% sulfuric acid.

[0101] Figure 7 is an SEM image showing the implant surface after sandblasting 150 μm size Al2O3 powder and then etching it at 80°C, 90°C, and 100°C for 10 minutes in a solution mixed with different weight parts of 30% hydrochloric acid and 25%, 35%, and 45% sulfuric acid.

[0102] Figure 8 is an SEM image showing the implant surface after sandblasting 150 μm size Al2O3 powder and then etching it at 80°C, 90°C, and 100°C for 15 minutes in a solution mixed with different weight parts of 30% hydrochloric acid and 25%, 35%, and 45% sulfuric acid.

[0103] Figure 9 is an SEM image showing the implant surface after sandblasting 250 μm size Al2O3 powder and then etching it at 80°C, 90°C, and 100°C for 5 minutes in a solution mixed with different weight parts of 30% hydrochloric acid and 25%, 35%, and 45% sulfuric acid.

[0104] Figure 10 is an SEM image showing the implant surface after sandblasting 250 μm size Al2O3 powder and then etching it at 80°C, 90°C, and 100°C for 10 minutes in a solution mixed with different weight parts of 30% hydrochloric acid and 25%, 35%, and 45% sulfuric acid.

[0105] Figure 11 is an SEM image showing the implant surface after sandblasting 250 μm size Al2O3 powder and then etching it at 80°C, 90°C, and 100°C for 15 minutes in a solution mixed with different weight parts of 30% hydrochloric acid and 25%, 35%, and 45% sulfuric acid.

[0106] FIGS. 3 to 11 measured the change in roughness according to the powder size used in the sandblasting step, the temperature and time conditions of the etching step, and confirmed that surface roughness is secured including micro pores within macro surface roughness within a short time and that multiple pores are included throughout the surface.

[0107] Figure 12 is a graph showing the change in roughness measured in Figures 3 to 11. Surface roughness can be determined by the size of the powder particles distributed in the blast process and the concentration of the acid etching solution. As shown in Figure 12, when the powder particle size is small (50 μm), the surface roughness after blasting is low. If the content of sulfuric acid contained in the acid etching solution is low at 25 parts by weight, there is a limit to increasing the surface roughness even if etching is performed, and the etching speed is slow, resulting in a longer process time. Conversely, if the content of sulfuric acid is high at 45 parts by weight, the surface roughness can be increased, but it is over-etched, resulting in an uneven shape and a change in surface color to black. Accordingly, it was confirmed that under the conditions of the present invention, a macroscopic roughness formed by sandblasting powder particles of size 200 μm to 300 μm is formed to a microscopic roughness of 2 μm to 4 μm in the shortest possible time by etching with an acid etching solution comprising 25 to 35 parts by weight of hydrochloric acid and 20 to 30 parts by weight of sulfuric acid. As a result, it was confirmed that the adhesive strength increases by providing a surface area that allows for easy bone integration and adhesion.

[0108] FIGS. 13 and 14 show the surface, cross-section, and bottom surface measured after sandblasting 150 μm size powder and etching the implant substrate with an acid etching solution containing 25 parts by weight of sulfuric acid at 80°C for 5 minutes, and then anodic oxidizing it in a solvent of ethylene glycol, 0.1 M NH4F, and 2.0 wt% H2O at 50 V for 30 minutes.

[0109] Figures 13 and 14 show an oxide film generated by anodic oxidation in the form of a nanotube, and a nanopattern may be generated as the oxide film is removed due to the oxide film uniformly generated under the conditions of the present invention.

[0110] FIGS. 15 to 23 show the surface formed by the nanopattern formed by the indentation after creating an oxide film by an anodic oxidation process on the surface measured in FIGS. 3 to 11 and removing the nanotube-shaped oxide film measured in FIGS. 13 to 14.

[0111] Figure 24 shows the pore size of the nanopattern layer formed on the surface after anodic oxidation. It was confirmed that the average pore size of the measured nanopattern layer was 109.99 nm.

[0112] FIG. 25 is a graph showing the change in roughness measured in FIG. 18 to FIG. 23. Surface roughness can be determined by the size of powder particles distributed in the blast process, the concentration of the acid etching solution, and the anodizing process conditions.

[0113] As shown in FIG. 25, it was confirmed that a nanopattern layer with a roughness of 1.5㎛ to 2.5㎛ was formed by anodic oxidation of the porous layer with a roughness of 2㎛ to 4㎛ measured in FIG. 12. As a result, it was confirmed that the adhesive strength is further increased by providing a surface area that allows for adhesion through improved biocompatibility and easy bone integration.

[0115] By combining Example 1 of the present invention and FIGS. 1 to 25, it can be confirmed that the implant of the present invention provides an implant with enhanced biocompatibility by forming a micro-roughness by etching a macro-roughness formed by sandblasting and forming a nano-pattern layer by anodic oxidation.

[0117] From the foregoing description, those skilled in the art to which the present invention pertains will understand that the present invention may be implemented in other specific forms without altering its technical concept or essential features. In this regard, the embodiments described above should be understood as illustrative in all respects and not restrictive. The scope of the present invention should be interpreted as including all modifications or variations derived from the meaning and scope of the claims set forth below and their equivalents, rather than from the detailed description above.

Claims

Claim 1 A method for manufacturing an implant comprising: a first step of forming a porous layer by etching after sandblasting on a titanium implant substrate; and a second step of forming a nanopattern layer on the titanium implant substrate having the porous layer formed thereon obtained from the first step; wherein the sandblasting treatment is performed by sandblasting powder particles with a size of 200 μm to 300 μm for 20 seconds to 40 seconds under pressure conditions of 3 kgf / cm2 to 5 kgf / cm2, and the nanopattern layer of the second step is formed after anodizing treatment and removal of an oxide film generated by anodizing; and wherein the implant comprises: a titanium implant substrate; and a porous layer including a plurality of pores formed on the surface of the titanium implant substrate. A manufacturing method comprising: a nanopattern layer formed on the porous layer; wherein the porous layer is formed with an average roughness (Ra) of 2 μm to 4 μm, the pore size of the nanopattern layer is 70 nm to 150 nm, the titanium implant substrate comprises Ti-6Al-4V, and the implant is formed with an average surface roughness (Ra) of 1.5 μm to 2.5 μm. Claim 2 delete Claim 3 delete Claim 4 delete Claim 5 An implant comprising: a titanium implant substrate manufactured by the method of claim 1; a porous layer comprising a plurality of pores formed on the surface of the titanium implant substrate; and a nanopattern layer formed on the porous layer; wherein the porous layer is formed with an average roughness (Ra) of 2 μm to 4 μm, the pore size of the nanopattern layer is 70 nm to 150 nm, the titanium implant substrate comprises Ti-6Al-4V, and the average roughness (Ra) of the implant surface is formed with 1.5 μm to 2.5 μm. Claim 6 delete Claim 7 delete

Citation Information

Patent Citations

  • The method of surface reforming using electrolytic polishing at the treated surface of titanium implant.

    KR101544357B1

  • Modification of implant surface with bioactive conjugates for improved integration

    WO1994026321A1

  • Implant having a surface nano-patterned groove and a method of manufacturing the same

    KR101724039B1

  • Method for Preparing Dental Implants with Improved Surface Morphology and Osseointegration

    KR101972122B1

  • Surface treatment process for implants made oftitanium alloy

    KR1020040099176A